Unreal words, real competition: Mandarin recognition slows for syllable-matched tonal gaps - Sharma, Bhamini; Li, Qun; Maggu, Akshay R. (Frontiers in Language Sciences, 2025)
Word recognition in tone languages like Mandarin is influenced not only by phonological structure but also by lexical tone. Prior research using auditory lexical decision tasks has shown that real monosyllables are generally processed more quickly and accurately than tonal gaps i.e., impossible syllable-tone combinations. However, these studies often did not control for syllable overlap between tonal gaps and real monosyllables, potentially underestimating lexical competition effects. The present study addressed this gap by contrasting real monosyllables, syllable-matched tonal gaps, and syllable-unmatched tonal gaps in a controlled auditory lexical decision task with 54 native Mandarin speakers. Results revealed that reaction times were significantly faster and accuracy higher for real monosyllables compared to both syllable-matched tonal gaps and syllable-unmatched tonal gaps. More importantly, syllable-matched tonal gaps elicited slower reaction times than syllable-unmatched tonal gaps, indicating increased lexical competition when tonal gaps share the same syllable as real monosyllables. These findings emphasize the critical role of phonological similarity and lexical competition in Mandarin word recognition. By controlling syllabic overlap, this study improves upon previous methodologies and offers a clearer assessment of auditory word processing in tone languages.